Factorial significance on tractor stability under variation of terrain roughness employing the Taguchi method - Li, Zhen; Zhu, Zhongxiang; Qin, Jiahao; Mao, Enrong; Mitsuoka, Muneshi; Inoue, Eiji; Shin, Soyoung (International Journal of Agricultural and Biological Engineering, 2018)
Tractor rollover accidents remain an issue with the development of agricultural mechanization. Adopting the scale-model-based experimental approach, this study investigated the three most influential geometric factors of tractor in various agricultural ground conditions with improved configuration of force sensing system. The initiation of tractor rollover, associated with the tire-ground contact status, was investigated for various front tire types, ballast weights, and rear track widths. Employing the Taguchi method, the ground reaction forces applied to the tractor’s uphill wheels were measured and evaluated using stability indicators. By taking this approach, the effects and statistical significance of the three factors and their interactions were examined under various agricultural ground conditions. Results showed that the ballast weight significantly affected the ground contact status of the uphill front tire. The significance of the front tire type gradually increased as the road roughness increased, but dramatically decreased for an extremely rough road surface. Furthermore, none of the factors or interactions, except the factor of the rear track width for relatively rough roads, was statistically significant. The study revealed that not all commonly discussed factors consistently affect tractor stability. The results of the present study are thus expected to provide a reference explaining how to explore the necessity and feasibility of parameter adjustment before reconfiguring a tractor for higher stability. Keywords: tractor rollover, scale model, agricultural fields, Taguchi method, factorial significance DOI: 10.25165/j.ijabe.20181105.3713 Citation: Li Z, Zhu Z X, Qin J H, Mao E R, Mitsuoka M, Inoue E, et al. Factorial significance on tractor stability under variation of terrain roughness employing the Taguchi method. Int J Agric & Biol Eng, 2018; 11(5): 88–94.